PENGARUH LIMBAH KULIT BUAH KAKAO SEBAGAI CAMPURAN MEDIA TANAM TERHADAP PRODUKTIVITAS DAN KANDUNGAN GIZI JAMUR TIRAM COKLAT (Pleurotus cystidiosus) - Imam Mudakir; Utami Sri Hastuti; Fatchur Rohman; Abdul Gofur (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract - The development of the plantation sector has increased impact of which waste wood sawdust and cocoa fruit peel. These wastes can cause environmental problems if not treated, but they would be beneficial if they are used as growing media mixture in oyster mushroom cultivation. Growing media (baglog) oyster mushrooms are supported physically and chemically will affect the productivity and nutrient content of oyster mushrooms. The study aims to analyze and assess the effect of the cocoa fruit peel waste as  growing media mixture on productivity and nutrient content of brown oyster mushroom (Pleurotus cystidiosus) that has been carried out using a completely randomized design (CRD) with 4 kinds of treatment comparisons sawdust and fruit peel waste cocoa, ie SL0(ratio of 100% wood sawdust and 0% fruit peel waste cocoa)/control, SL1 (ratio of 80% sawdust and 20% fruit peel waste cocoa), SL2 (ratio of 75% sawdust and 25% fruit peel waste cocoa) and SL3 (ratio of 70% sawdust and 30% fruit peel waste cocoa). The research data in the forms of number and weight of fruit body production, as well as protein and fat content of brown oyster mushrooms, were then analyzed by one-way anova and followed by DMRT (Duncan Multiple Range Test)  at 5%. The results showed that the use of cacao fruit peel waste by ratio comparison  75% wood sawdust and 25% cacao fruit peel (SL2) is the best to produce the number and weight of fruit body production as well as protein and fat content of brown oyster mushrooms. Therefore, it is recommended to be applied in the cultivation of brown oyster mushroom. Keywords: wood sawdust , growing media, productivity, nutrition, brown mushrooms